Optimization on the Budgeting Allocation with Goal Programming in Departmen Mathematic Education Universitas HKBP Nommensen - Sihombing, Dame ifa (ZERO: Jurnal Sains, Matematika dan Terapan, 2023)
The purpose of this research is to maximize the use of funds at the Universitas HKBP Nommensen Faculty of Training and Educational Sciences, a higher education establishment.  This study intends to educate the general public on the use of goal programming challenges in achieving organizational goals, both financially and non-financially. Between 2020 and 2022, information on this faculty's budget estimates was gathered from the faculty budget. Five objectives were taken into consideration for the study in the following order of priority: personal costs, overhead costs, capital expenditures, revenue (internally generated), and the total budget from the university's budget estimates. The information gathered was utilized to create a goal programming problem, which was then addressed using the Simplex approach (using LINGO software). The optimum value of Z (Z=4.24) was found to achieve goal 1 (the personal cost goal), goal 3 (the capital expenditure goal), and goal 5 (the overall budget goal) based on the solution provided. However, it failed to satisfy goals 2 and 4, which are the goals for overhead costs and revenue, respectively. Based on the results, it was determined that in order to meet targets 2 and 4, which are related to overhead costs and revenue, respectively, the Department Mathematic Education Universitas HKBP Nommensen, needed to come within 4.24 billion Rupiah. It was also suggested that the University have an annual budget review with a minimum of 4.24 billion Rupiah in 2010 and that this review be done in a timely and appropriate manner, under the supervision of an active government budget monitoring team.